2007
DOI: 10.1111/j.1365-2788.2006.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the balance capabilities of people with profound intellectual disabilities who have experienced a fall

Abstract: The reason why people with ID frequently fall appears complex and multifactorial. Larger studies are required to verify the potential risk factors identified in this pilot study. Many of the standardized outcome measures commonly used in physiotherapy practice to quantify balance capabilities are not suitable for use in this population group, as participants found it difficult to comprehend what was required of them. Allowing the person to become familiarized with both the test and the tester may help to allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 37 publications
7
126
2
4
Order By: Relevance
“…Adults with DS may experience an increased risk of falling at an earlier age than their peers with TD as they face multiple constraints to walking stability earlier in life. Our findings so far are in agreement with Hale and colleagues [41], who concluded that the increased risk of falling in adults with various intellectual disabilities is multi-factorial. In future research, we plan to explore the link between decreased stability and risk of falling in adults with DS, as well as the effectiveness of intervention to increase overall stability.…”
Section: Resultssupporting
confidence: 93%
“…Adults with DS may experience an increased risk of falling at an earlier age than their peers with TD as they face multiple constraints to walking stability earlier in life. Our findings so far are in agreement with Hale and colleagues [41], who concluded that the increased risk of falling in adults with various intellectual disabilities is multi-factorial. In future research, we plan to explore the link between decreased stability and risk of falling in adults with DS, as well as the effectiveness of intervention to increase overall stability.…”
Section: Resultssupporting
confidence: 93%
“…This finding reflects a proprioceptive deficit for this group. In addition, as individuals with ID age, lifestyle and health-related problems also contribute to postural instability and often increase the risk of falls and of loss Stabilization of Posture and Intellectual Disability 209 of independence (Hale, Bray, & Littmann, 2007). Lahtinen, Rintala, and Malin (2007), reporting a 30-year longitudinal study of individuals with ID, found that in adolescence, 25% of the ID participants were able to complete a static balance task (standing on one foot for 60 s, i.e., stork stand test); in adulthood the total of those who could perform the task dropped to less than 10%.…”
mentioning
confidence: 99%
“…Earlier studies have shown that children with mild ID are markedly inferior compared to nonhandicapped children when performing one foot static balance test (Howe 1959). As analyzed below, more recent studies verify that individuals with ID have a significantly deteriorated balance capacity and reduced ability to respond to external balance perturbations (Carvalho and Almeida 2009;Dellavia et al 2009;Enkelaar et al 2012;Galli et al 2011;Gomes and Barela 2007;Hale et al 2007;Hale et al 2009;Ko et al 1992;Kokubun et al 1997;Lahtinen et al 2007;Okuzumi et al 1997;Rigoldi et al 2011;Smith and Ulrich 2008;Suomi and Koceja 1994;Van De Vliet et al 2006;Van Emmerik et al 1993;Vuijk et al 2010;Webber et al 2004;Yanardag et al 2013). …”
Section: Balancementioning
confidence: 82%